(untitled) (Herald of Journalism, 2022)
Relevance of the research work. Journalism is becoming the main component in solving global problems, changing its principles and functions in the world space. The mass media also needs a more constructive and intensive dialogue between representatives of different ethnic groups, cultures, political forces, and religions in order to consolidate the moral orientation of society. Based on this, it is possible to achieve maximum consensus in world actions, mutual understanding between civil society institutions and power structures. Research topic. The article is based on the history, function, trends and professional standard of domestic military journalism. When it comes to the place of military journalism in the media system, it covers the conflicting aspects of world political processes. The purpose of the research paper is to show the current state of relations between the media and the military. In the relationship between the military and the media, the soldiers ’ emphasis on the secrecy of the operation and the demands of the media for freedom of information create a natural conflict. Scientific novelty and practical significance. The scientists themselves did not know the main provisions and theoretical understanding of the military topic. The scientific novelty and practical significance of the work is that it is here that the media take this military theme to a new level. Solving current scientific problems, assessing the state of affairs. The main goal of military journalism is to convey a branded topic to the target audience. Therefore, this study aims to solve current scientific problems and assess the state of affairs. After analyzing the above, we think that our work can contribute to solving current scientific problems and assessing the state of affairs within the framework of this topic. Keywords: military journalism, conflict zone, emotional elements, trends, professional standards.